2012
DOI: 10.18553/jmcp.2012.18.9.690
|View full text |Cite
|
Sign up to set email alerts
|

Generic Drug Discount Programs: Are Prescriptions Being Submitted for Pharmacy Benefit Adjudication?

Abstract: BACKGROUND: In 2006, pharmacies began offering select generic prescription drugs at discount prices (e.g., $4 for a 30-day supply) through nonmembership and membership programs. As part of the contract in membership generic drug discount programs, the member agrees to forgo submission of the claim to the insurance company. Claims not submitted for insurance adjudication may result in incomplete pharmacy benefit manager (PBM) and health plan data, which could negatively influence adherence reporting and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Other studies have also found that claims databases fail to capture dispensings . These studies have used a diverse set of designs, data sources, and focus of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also found that claims databases fail to capture dispensings . These studies have used a diverse set of designs, data sources, and focus of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found that claims databases fail to capture dispensings. 10 These studies have used a diverse set of designs, data sources, and focus of interest. They include studies using commercial claims databases to compare the proportion of subjects exposed to a specific drug in different time periods to infer missing dispensings 11 ; using the Medical Expenditure Panel Survey to quantify the degree of use of low-cost generic programs to infer the degree of missing dispensing in claims databases 12,13 ; using self-report medication use to assess lack of capture in claims databases 14 ; and examining the impact of drug samples provided by physician offices on drug exposure misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…28 A survey among predominantly insured patients found that only 4.7% of respondents used a GDDP in 2008, 29 and the use of these programs was likely greater in uninsured populations. 27,29 Our exclusion of patients with no prescription claims during the entire study may partially address this potential misclassification bias. Finally, we were not able to detect if patients were nonusers because they were not prescribed a β-blocker or because they chose not to fill a prescription, an important distinction in addressing underutilization of this therapy.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…4, 15, 16 Based on Medical Expenditure Panel Survey (MEPS) self-reports of medication fills/ expenditures merged with Part D claims, researchers concluded that people tended to over-report the number of fills per medication (possibly due to reporting free samples from providers) but to underreport the number of medications. 17 However, the data were from 2006–2007, which was at the start of the expansion of GDDP plans, and the study excluded veterans since federal pharmacies (including VA pharmacies) do not file Part D claims.…”
Section: Introductionmentioning
confidence: 99%